Education and public outreach through vacuum science and technology. (February 2022) - Riccardi, P.; Romano, V.; Pellegrino, F.
Abstract: The need to communicate with the public is widely known within the broadest scientific community and education and public outreach have become important aspects in the working life of research scientists. Since vacuum equipment are present in many research laboratories world-wide, vacuum is an excellent topic for education and public outreach activities with schools, that can favor a large involvement of researchers, supporting a sustained interaction of researchers with school pupils and teachers. We illustrate activities focused on vacuum technologies that connect the history of science to actual research topics and to the curricula of several school disciplines. Highlights: We illustrate education and public outreach (E/PO) activities with schools focused on vacuum technologies and their history. E/PO has become an important aspect of the working life of research scientists. vacuum is an excellent topic for E/PO activities with schools, that can favor a large involvement of researchers. The activities connect the history of physics to actual research topics and to the curricula of several school disciplines.